STRATEGI PENGEMBANGAN USAHA DALAM MEMENUHI KEBUTUHAN KONSUMEN MENGGUNAKAN ANALISIS SWOT PADA AIR GALON MINERAL OSMO PLUS - Ade Hadiono; Firzah, Putri (LPPM STIA Banten, 2024)
ordinary water treatment technology into ready-to-drink water makes many parties encouraged to exploit water and packaged into drinking water in bottles both silly size to 19 liter gallon size. This study aims to determine the business development strategy on Osmo Plus gallon water. The research method uses a quantitative descriptive approach. The population of this study was regular consumers of Osmo Plus gallons of water, a sample of which was used by 80 respondents. While the technique used is random sampling. Data collection techniques with observation, questionnaire, interview, literature study and documentation methods. The data analysis technique used is SWOT analysis, where data is collected based on conclusions drawn from the SWOT matrix. From the calculation of the SWOT matrix, there are values in the SO strategy (0.36,0.38), WO strategy (0.33,0.38), ST strategy (0.36,0,27) and WT strategy (0.33,0,27).